Competition and Bank Risk the Role of Securitization and Bank Capital - Altunbas, Yener (IMF Working Papers; Working Paper ;, 2019)
We examine how bank competition in the run-up to the 2007-2009 crisis affects banks' systemic risk during the crisis. We then investigate whether this effect is influenced by two key bank characteristics: securitization and bank capital. Using a sample of the largest listed banks from 15 countries, we find that greater market power at the bank level and higher competition at the industry level lead to higher realized systemic risk. The results suggest that the use of securitization exacerbates the effects of market power on the systemic dimension of bank risk, while capitalization partially mitigates its impact.